2023
DOI: 10.1071/mf23095
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of nematode larvae found in a vulnerable native Australian fish, the southern pygmy perch, Nannoperca australis Günther

Abstract: Context The southern pygmy perch (Nannoperca australis) is an endemic freshwater fish in Australia that is facing population decline and is listed as endangered or vulnerable in several states. Aims The aim of this study was to investigate the presence of parasites in the southern pygmy perch population and provide insights into their effect on the health and conservation of the species. Methods In total, 81 southern pygmy perch specimens were examined for parasite infections, followed by charact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…More specifically, Pettersen et al [44] observed that minnow parasites were similar between introduced and native areas in Norway (although this study only focused on the ectoparasitic genus Gyrodactylus). To test for potential limitations of the present study, visual examinations alone may result in underestimation of parasite detection/abundance, as observed by Shamsi et al [45]. In the present study, two parasite species were not detected in some seasons (the digenean Hysteromorpha triloba and the nematod Raphidascaris acus), in spite of their life-spans being longer than a single season (three months) [46].…”
Section: Discussionmentioning
confidence: 41%
“…More specifically, Pettersen et al [44] observed that minnow parasites were similar between introduced and native areas in Norway (although this study only focused on the ectoparasitic genus Gyrodactylus). To test for potential limitations of the present study, visual examinations alone may result in underestimation of parasite detection/abundance, as observed by Shamsi et al [45]. In the present study, two parasite species were not detected in some seasons (the digenean Hysteromorpha triloba and the nematod Raphidascaris acus), in spite of their life-spans being longer than a single season (three months) [46].…”
Section: Discussionmentioning
confidence: 41%
“…Additionally, due to the limitation of visual examination employed in this study, some nematode larvae, such as Contracaecum spp. and Spiroxys spp., with a low infection rate in C. nasus may be overlooked [34][35][36].…”
Section: Discussionmentioning
confidence: 99%